IDEOLOGY IN ADVERTISING DISCOURSE: A MULTIMODAL ANALYSIS APPROACH - Agung Farid Agustian (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
The multimodal analysis tries to analyze the practice of semiotic discursive or non-discursive discourse such as language, visual images, materials, and architecture. The tool for analyzing semiotic objects is one of the analytical tools in systemic functional linguistics (SFL). The formulation of the problem in this study is the form of representation of ideas in advertising discourse based on the meaning and function of grammatical semantics. Specifically, the research question is the ideology in advertising discourse in ideational, interpersonal, and textual aspects. This study tries to analyze the multimodal element to explain the choice of linguistics and the object of discourse. This research is descriptive qualitative where takes the inductive paradigm. This research approach is critical multimodal discourse analysis with systemic functional linguistic analysis. The research data is in the form of beauty product advertisements in 2017. The results show that the meaning of beauty product advertisements in terms of physical characteristics is white skin colour, sharp nose, slender body, long hair, and white teeth. The concept of ethnically beautiful identity from the two advertisements is different. The local product advertisements emphasize ethnic captivating identity. Foreign beauty product advertisements representations emphasize fair Caucasian beauty.